Chemical Analysis of a Fodder Tree Leaves (Terminalia tomentosa) - Rawat, Shiwani; Singh, C.P.; Rawat, G.S. (Asian Journal of Chemistry, 2010)
Protein, crude protein, ether extract, crude fibre, ash, insoluble silica, carbohydrate, sugars, reducing sugars, minerals, trace elements and amino acids were found in the leaves of the plant.